Implementasi Program Kartu Prakerja di Kecamatan Posigadan Kabupaten Bolaang Mongondow Selatan - Febriani Helingo; Zuchri Abdussamad; Yacob Noho Nani (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2026)
The Pre-Employment Card Program is a government policy that aims to improve people's work competencies through digital-based training to support human resource development and reduce unemployment. The implementation of programs in the regions still faces various challenges, especially in areas that have limited access to technology and infrastructure. This study aims to analyze the implementation of the Pre-Employment Card Program in Posigadan District, South Bolaang Mongondow Regency based on the perspective of policy implementation. The research uses a qualitative method with a descriptive approach. Observations, documentation, and thorough interviews were used to obtain the data. The Miles and Huberman model is used to perform data analysis, which includes data presentation, conclusion drawn, and data reduction. The results of the study show that the Pre-Employment Card Program in Posigadan District has been implemented quite well and helps the community by increasing knowledge and incentive assistance. However, the implementation is not fully optimal because there are still obstacles in terms of communication, resources, implementation disposition, and bureaucratic structure. The socialization of the program has not reached the entire community effectively. Limited internet access and supporting facilities are still the main obstacles. Coordination between agencies has also not been running optimally. This research implies the need to increase direct socialization, strengthen digital infrastructure support, increase assistance to participants, and strengthen coordination between institutions so that the goals of the Pre-Employment Card Program can be achieved more effectively.